Advances in hexitol and ethylene glycol production by one-pot hydrolytic hydrogenation and hydrogenolysis of cellulose. (March 2015) - Li, Yuping; Liao, Yuhe; Cao, Xiaofeng; Wang, Tiejun; Ma, Longlong; Long, Jinxing; Liu, Qiying; Xua, Ying
Abstract: In this review, recent advances in the one-pot hydrolytic hydrogenation and hydrogenolysis of cellulose to value-added polyols, including hexitols (sorbitol, mannitol, and isosorbide) and 1, 2-alkanediols (ethylene glycol and 1, 2-propylene glycol), are summarized. Methods for the generation of H + in the first step of cellulose hydrolysis to form intermediate sugars, such as the use of soluble acids (mineral acids and heteropoly acids) and H + produced in situ from functional supports and H2 dissociation, are classified and analyzed, considering its combination with active metals for the subsequent hydrogenation or hydrogenolysis of sugars to polyols. The interaction of non-noble metals such as nickel, bimetals, and tungsten with support materials in the catalytic conversion of intermediate sugars to hexitols and ethylene glycol is reviewed. The corresponding reaction pathways and mechanisms are discussed, including the conversion process using basic supports and solution conditions. Major challenges and promising routes are also suggested for the future development of the chemocatalytic conversion of cellulose. Highlights: Advances in the one-pot hydrolytic hydrogenation/hydrogenolysis of cellulose are summarized. The interaction of non-noble metals with support materials for cellulose conversion is reviewed. Method for the generation of in situ H + and effects of the acidic groups on supports are discussed. Incomplete identification of intermediates/products causes mechanism complications. Efficient conversion, separation and purification are other concerns for cellulose degrading.